Un artifex di Pheradi Maivs? A proposito di una scultura fittile del santuario di Thinissut (Africa Proconsularis) - Zucca, Raimondo (Gerión. Revista de Historia Antigua, 2005)
In Thinissut site in Bir Bou Rekba, near bon Cape, was discovered at the beginning of the XX century, a punic-roman sanctuary dedicated to Baal Hammon and Tanit-Caelestis, which contained, even in fragmentary, the sanctuary terracotta statues of the cult. Tanit was represented like a lionhead goddess with a latin inscription incised before baking.In this occasion we present a new interpretation of the epigraph which leads to ascribe the statue at artifex of Phaeradi Maius, Saturninus, P(ublii) Fil(ius). Paleographic fonts of the inscription allow to ascribe a datation within the giulio-claudia age, maybe to limited in the period of Augustus; perhaps that is the age of the terracotta statue produced by the roman Africa Handicraft, with eastern archaic iconographic elements and more recent lessons of style from the late hellenic period.
Keywords: Sanctuary; Thinissut; Lionhead goddess; Terracottas statues; Pheradi Maius